THE INFLUENCE OF THIRD PARTY FUNDING, CAPITAL ADEQUACY RATIO AND NON PERFORMING FINANCING ON COMPANY PROFITABILITY - Elwisam; Melati; Muhani; Kumba Digdowiseiso (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to investigate the influence of third party funds, Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF) on company profitability in the context of Islamic banking and finance. Using a Systematic Literature Review (SLR) approach, this research identified 10 relevant accredited national journals via Google Scholar and the "Publish or Perish" application. Inclusion and exclusion criteria were applied to ensure the quality of the selected journals. The results of the analysis and summary of the selected journals are presented in a table, showing the main findings, research methodology and conclusions. The first finding shows that TPF, CAR, and NPF have a positive influence on financing and profitability. The next findings illustrate the impact of NIM, NPL, and CAR on banking company value, with NIM and NPL having a significant influence, while CAR has a positive influence. Other research highlights the importance of effective management of variables such as NPF, FDR, CAR, BOPO, and Bank Size in increasing the profitability of the financial sector. The discussion describes the analysis of the findings, including the complex relationships between variables. Several studies show that NPF can influence ROA, while FDR can affect bank liquidity efficiency. CAR is identified as a key factor in increasing profitability by absorbing the risk of loss. BOPO also plays an important role, with a low ratio indicating management efficiency and potential for increased ROA. This research provides a comprehensive picture of the impact of certain variables on company profitability in the financial sector. The implications include the importance of effective management of risk and liquidity, as well as the need for an in-depth understanding of these variables to improve the company's financial performance.